Air quality and mental illness: role of bioaerosols, causal mechanisms and research priorities - Bhui, Kamaldeep; Ucci, Marcella; Kumar, Prashant; Jackson, Simon K.; Whitby, Corinne; Colbeck, Ian; Pfrang, Christian; Nasir, Zaheer A.; Coulon, Frederic (Royal College of Psychiatrists, 2024)
Background: Poor air quality can both trigger and aggravate lung and heart conditions, as well as affecting child development. It can even lead to neurological and mental health problems. However, the precise mechanisms by which air pollution affect human health are not well understood. Aims: To promote interdisciplinary dialogue and better research based on a critical summary of evidence on air quality and health, with an emphasis on mental health, and to do so with a special focus on bioaerosols as a common but neglected air constituent. Method: A rapid narrative review and interdisciplinary expert consultation, as is recommended for a complex and rapidly changing field of research. Results: The research methods used to assess exposures and outcomes vary across different fields of study, resulting in a disconnect in bioaerosol and health research. We make recommendations to enhance the evidence base by standardising measures of exposure to both particulate matter in general and bioaerosols specifically. We present methods for assessing mental health and ideal designs. There is less research on bioaerosols, and we provide specific ways of measuring exposure to these. We suggest research designs for investigating causal mechanisms as important intermediate steps before undertaking larger-scale and definitive studies. Conclusions: We propose methods for exposure and outcome measurement, as well as optimal research designs to inform the development of standards for undertaking and reporting research and for future policy.
Keywords: 3202 Clinical sciences; 4203 Health services and systems; Bioaerosols; exposure; health impacts; air pollution; indoor and outdoor air